BOOSTING MATH SCORES IN ELEMENTARY SCHOOLS WITH THE INDEX CARD MATCH METHOD - Ai Wartini; Aristocrat Aristocrat; Halimah Halimah (Journal of Learning on History and Social Sciences, 2024)
Increasing student learning outcomes is greatly influenced by motivation in the learning concept. Teachers can achieve this by using appropriate learning methods. The aim of this research is to increase student motivation and learning outcomes in mathematics lessons. One of the efforts made by teachers to increase students' learning motivation in Mathematics subjects is by applying methods Index Card Match. This research used a Classroom Action Research (PTK) approach and involved 26 class II students at SDN Cijagra 04, Paseh District, consisting of 13 female students and 13 male students. The research was conducted in 2 cycles during the 2023-2024 academic year. If the subject's score in the first cycle has not reached the Minimum Completion Criteria (KKM) score, the research will continue in the second cycle. If all subjects achieve scores according to the KKM in the second cycle, the research is considered complete. After 2 cycles, student learning outcomes increased from 86.69 in cycle 1 to 100 in cycle 2. Data analysis used qualitative and quantitative approaches. The research conclusion shows that there is an increase in students' motivation and mathematics learning outcomes by implementing the Index Card Match method. Students also show enthusiasm, enthusiasm, activity, creativity and courage in expressing opinions. Student motivation towards learning material also increases, and student learning experiences become broader, which ultimately has an impact on improving learning outcomes. It is hoped that the results of this research can help teachers choose appropriate learning methods to achieve learning goals, especially in Mathematics subjects